GEANT4 models for the secondary radiation flux in the collimation system of a 300 MeV proton microbeam. Issue 12 (December 2016) - Dou, Yanxin; Jamieson, David N.; Liu, Jianli; Li, Anlong; Li, Liyi
Highlights: A bending collimation system to reduce the collimator scattering in a 300 MeV proton microbeam is proposed. The influences of collimator material and proton energy in the bending collimation system are systematically invested. The limitation of vacuum pressure is invested for a 300 MeV proton microbeam. Abstract: In Harbin, we are developing a 300 MeV proton microbeam for many applications in space science including upset studies in microelectronic devices, radiation hardness of materials for satellites and radiation effects in human tissues. There are also applications of this facility proposed for proton therapy. The microbeam system will employ a purpose-built proton synchrotron to provide the beam. However there are many challenges to be addressed in the design, construction and operation of this facility. Here we address two important design aspects for which we apply GEANT4 modeling. First, the high energy proton beam interacts strongly with beam line materials, especially the collimation slits, to produce showers of secondary particles which could introduce significant background signals and degrade the resolution of the proton microbeam. Second, the beam transport within the residual vacuum of the beam line may also introduce undesirable background radiation. In both cases mitigation strategies need to be incorporated during the design phase of the new system. We study the use of a dipole magnet following the aperture collimator to reduce the flux of secondary particles incident on the analysis chamber. Monte Carlo simulations are performed using GEANT4 and SRIM. By inserting the dipole magnet, we find as expected a significant reduction in the scattering of protons and other particles, such as neutrons and gamma rays, at the collimation system exit position. Secondary radiation from the residual gas pressure within the beam line vacuum system are also modelled and found to be negligible under the standard operating conditions.